Teacher strategies in online learning to increase students’ interest in learning during COVID-19 pandemic - Sutarto Sutarto; Dewi Purnama Sari; Irwan Fathurrochman (Jurnal Konseling dan Pendidikan, 2020)
Interest has a very important role in learning. This interest leads to motivation in learning and it can improve learning outcomes. This study focused on understanding and exploring the strategies used by teachers of SDIT Rabbi Radhiyya Curup to increase student's interest in learning and to express students' responses in Online learning during the COVID-19 pandemic. This research is qualitative research with a phenomenological approach in which the principal, the vice-principal of curriculum, the teachers, and students were the informants of this research. The data were collected by conducting semi-structured interviews which were analyzed by using the Miles and Huberman model. The results showed that the strategies used by the teacher to increase students' interest in learning were to provide students with an understanding of the importance of learning, to make learning material brief, clear, and interesting, to use simple and interesting media, and to conduct regular and continuous evaluations. Online learning, students get something fun, but they lack togetherness with their friends.